2005
DOI: 10.1111/j.1538-7836.2005.01343.x
|View full text |Cite
|
Sign up to set email alerts
|

The expression of prion protein (PrPC) in the megakaryocyte lineage

Abstract: ) is a naturally occurring protein in normal individuals which adopts an abnormal conformation, termed scrapie prion protein (PrP Sc ) that is associated with disease. There is great concern that clinically asymptomatic variant Creutzfeldt-Jacob disease (vCJD) may transmit PrP Sc in blood transfusion products. PrP C is widely expressed and has been found in human blood. The majority of cellular borne PrP C is associated with platelets (84%). Although PrP C mRNA has been demonstrated in platelets, the quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 26 publications
2
20
0
1
Order By: Relevance
“…The current study localizes PrP C to platelet alpha granule, but not dense granule, membranes, confirming a recent study by Starke et al 9 Thus, PrP C is present with proteins such as the ␣IIb/␤3 integrin, CD62 (P-selectin), CD36, and the GPIb/V/IX complex [32][33][34][35] inherent in the alpha granule membrane, and, in common with these other proteins, there is an activation-mediated increase in expression of PrP C on the external platelet surface. The function of PrP C in platelets is unknown; preincubation with anti-PrP C Abs has a limited effect on platelet adhesion to a variety of matrices but no effect on agonist-induced aggregation (Robertson et al, unpublished); therefore, it is unlikely that PrP C plays a significant role in either of these platelet functions.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The current study localizes PrP C to platelet alpha granule, but not dense granule, membranes, confirming a recent study by Starke et al 9 Thus, PrP C is present with proteins such as the ␣IIb/␤3 integrin, CD62 (P-selectin), CD36, and the GPIb/V/IX complex [32][33][34][35] inherent in the alpha granule membrane, and, in common with these other proteins, there is an activation-mediated increase in expression of PrP C on the external platelet surface. The function of PrP C in platelets is unknown; preincubation with anti-PrP C Abs has a limited effect on platelet adhesion to a variety of matrices but no effect on agonist-induced aggregation (Robertson et al, unpublished); therefore, it is unlikely that PrP C plays a significant role in either of these platelet functions.…”
Section: Discussionsupporting
confidence: 80%
“…7 In the former case the surface expression of PrP C is increased following stimulation, suggesting an additional internal membrane source of the protein, 8 recently shown to be alpha granule membranes. 9 Furthermore, platelet activation is associated with the accumulation of PrP C in releasates, 10 and in platelet concentrates, stored for up to 10 days, there is an increase in initially the microsomal, then plasma levels of PrP C . 11 Transmissible spongiform encephalopathies (TSEs) are a family of neurodegenerative disorders, including CreutzfeldtJakob disease (CJD), Gerstmann-Straussler-Schienker syndrome, and fatal familial insomnia in humans; scrapie in sheep; and bovine spongiform encephalopathy (BSE) in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work showed that several types of blood cells express PrP, albeit at vastly different levels: lymphocytes, dendritic cells, monocytes, granulocytes, erythrocytes, platelets, certain lymphoid precursors, and CD34 ؉ cells, which in humans are an enriched stem͞progenitor cell population (7,(24)(25)(26)(27). However, it was unknown whether PrP is expressed on HSCs with repopulating activity, and there was no indication of a possible function of PrP in any of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…PrP C is produced endogenously by cells of the platelet lineage, which could implicate platelets in PrP RES propagation or trafficking within the body or transmission in contaminated blood products (11,34,35,37,48). Forty-three to 53%, 63 to 95%, and 69 to 93% of bovine (3), ovine (4), and white-tailed deer (unpublished findings) platelets, respectively, express PrP C , and given the number of circulating platelets versus the number of leukocytes, the majority of blood-borne PrP C expression is platelet associated (11,48,71). This blood component could be largely responsible for the transmission of vCJD by transfusion (45,46).…”
Section: Interval To Detection Of Cwd Infection By Tonsil Biopsymentioning
confidence: 93%